The recognition and management of early psychosis : a preventive approach - McGorry, Patrick D.; Jackson, Henry J. (Cambridge University Press, 1999)
This is the first text to focus on the preventive potential of early detection of psychosis, and the practicalities of intervention. Incorporating many personal narratives and case histories, it is strong on theory, sensitive on practical issues, and will challenge, inform and guide clinicians.